Migrants et contrebande de monnaies en Roussillon dans la première moitié du xve siècle - Margault Coste (Les Cahiers de Framespa)
This article presents eight cases of smuggling of prohibited coins, seized from migrants by the guards of the ports and passages administration in Roussillon, during the reign of Alphonse the Magnanimous (1416-1458), a period marked by a strengthening control of the border with Languedoc. The judicial sources revealed here have been supplemented by regulations concerning the circulation of currencies and by administrative documentation relating to border surveillance. Whereas the normative framework depicts borders as obstacles for migrants, this ground-level study shows that the latter also have the capacity of putting borders to the test by testing their resistance, their porosity, and their flaws.